Recent Developments in the Cost of Debt Capital: Discussion - Yawitz, Jess B. (Journal of Finance, 1978)
Jess B. Yawitz, Recent Developments in the Cost of Debt Capital: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 881-883